Two-Dimensional Gas Chromatography-Mass Spectrometry to Determine Composition of the Products of Waste Tire Pyrolysis - Gertsiuk, M.M.; Kovalchuk, T.; Kapral, K.; Lysychenko, G.V. (Science and Innovation, 2024)
The method of two-dimensional gas chromatography coupled with mass-spectrometry detection has been used for deter mination of pyrolysis liquid which is a mixture of waste tire pyrolysis products. Six and a half thousand organic compounds have been identified: saturated, unsaturated, and aromatic hydrocarbons, as well as derivatives of thiophene, and cyclic amino-compounds. The pyrolysis liquid is similar to the diesel fuel by its composition and can be used as alternative fuel.